Risk of Work Accidents Due to Work Attitude in Speedboat Crews - Saputri, Asih Isni; Febriyanto, Kresna (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction:A work accident is an unwanted event that can result in loss that occurs at work. Workplace attitude incompatibility leads to fatigue and a variety of complaints, all of which contribute to the occurrence of work-related accidents. The purpose of this study is to determine whether there is a relationship between work attitude and the risk of work accidents among speedboat crew members at SDF Port, Tarakan City. Methods: This research used quantitative analysis with a cross-sectional design. Data were obtained through questionnaires and direct interviews. This research population is the speedboat crew at the Port of SDF Tarakan City; a total of 130 crew members were sampled using a non-probability sampling technique with the accidental sampling method. This study used the Chi-Square test to perform the statistical analyis. Results: As many as 64.6% of workers were involved in an accident, with the majority of them slipping. In contrast, 85 workers (65.4%) have the incorrect work attitude. Conclusion: It can be concluded that there is a significant relationship between work attitude and the risk of accidents among speedboat crews. The ship's management should make guidelines regarding working in a speedboat. Briefings before and after work are also one of the solutions for ensuring the crew members work according to predetermined standards.